Study on the inactivation and reactivation mechanism of pathogenic bacteria in aquaculture by UVC-LED - Zhang, Weixiao; Huang, Ruipin; Zhang, Tao; Wang, Baolong; Li, Na; Sun, Yan; Ma, He; Zhang, Qian; Zhang, Junxin; Liu, Ying (Frontiers in Marine Science, 2023)
Ultraviolet disinfection is an important method for controlling the large-scale outbreaks of diseases in aquaculture. As a novel and promising light source, ultraviolet light-emitting diode (UV-LED) has the advantages of safety, high efficiency and no environmental pollution risks. However, it remains unclear whether UV-LEDs can replace traditional UV light sources for aquaculture water treatment processes. Present study aimed to investigate the efficacy of UVC-LEDs (265 nm) on pathogenic bacteria, specifically Aeromonas salmonicida and Escherichia coli. The effects of UVC-LED dose, light conditions, and temperature on bacterial reactivation were also investigated. The results showed that exposure to UVC-LED effectively inactivated both types of bacteria. To achieve 4.5-log inactivation of A. salmonicida and E. coli, 24 mJ/cm2 and 28 mJ/cm2 UVC-LED irradiation were required, and the inactivation rate increased with increasing UVC-LED fluence. Both A. salmonicida and E. coli were revived after UVC-LED disinfection, and photoreactivation was significantly higher than dark reactivation. Bacterial reactivation rate due to high-dose UVC-LED treatment was significantly lower than that of low-dose. After 72 h of reactivation, photoreactivation and dark reactivation rates were 1 ± 0.4% and 2.2 ± 0.2%for A. salmonicida, and 0.02% and 0% for E. coli, respectively. Besides, the photoreactivation rates for the two bacteria exhibited different correlations with temperature. The highest photoreactivation rate for A. salmonicida was 68.7 ± 4% at 20°C, while the highest photoreactivation rate for E. coli was 53.98 ± 2.9% at 15°C for 48 h. This study reveals the rapid and efficient inactivation of bacteria by UVC-LED, and elucidates the mechanism and influencing factors for inactivation and reactivation by UVC-LED. The study also highlights that adequate UVC-LED irradiation and avoidance of visible light after UVC-LED disinfection can effectively inhibit bacterial reactivation. Our findings form a reference for the design and operation of UV disinfection in aquaculture.